The relationships of team diversity, social capital and ambidexterity - NG, Hock Seng (Institutional Knowledge at Singapore Management University, 2018)
This study seeks to gain insights into the impact of team diversity on building ambidextrous teams, i.e., managing trade-offs of “exploiting the present” and “exploring the future.” Given the inconsistent findings of the effects of diversity on team outcomes to date, the effect (if any) will likely be mediated and/or moderated by contextual factors. Hence, in this study, I have examined team social capital to understand better its role in fostering the relationship between team diversity and team ambidexterity. The results of this empirical study using 211 work teams (include 1,342 managers and employees) from two multi-national companies spanning fourteen countries showed that both team diversity and team social capital are reliable predictors of team ambidexterity. While the business case for diversity appears to be a “no-brainer” for most researchers and managers alike, but the formation of diverse teams will not automatically lead to team ambidexterity. Unlike many other forms of capital, social capital increases rather than decreases with use. So, it is important for organizations to pay equal, if not more, attention on building and nurturing team social capital.